A Review of Avifaunal Diversity of Dehang Debang Biosphere Reserve, Arunachal Pradesh - Rangini, N.; Lodhi, Mahendra S.; Palni, L. M. S.; Chaudhry, Shivaji; Samal, P. K. (Indian Forester, 2014)
Avifauna in and around the Dehang Debang Biosphere Reserve exhibits a wide range of diversity. A total of 492 avifaunal species were recorded in and around DDBR belonging to 237 genera, 18 orders and 71 families. The study reveals that out of the 492 species, 287 species (58.2%) belongs to order Passeriformes, the largest and most diverse order of birds, which is found worldwide and least contributed by the order Psittaciformes, 37 (7.5%) species has been identified as threatened globally (IUCN Red List Categories and Criteria version 3.1) while the 454 species (92%) are at least concern status with population of some of the species decreasing due to various causes like habitat degradation and hunting, this continued decrease in the population may result in extinction of such species in near future.